An exploration of Social Networking Sites (SNS) adoption in Malaysia using Tecnology Acceptance Model (TAM), theory of planned behavior (TPB) and intrinsic motivation - Mohd Zulkifli Muhammad; Goh Say Leng; Suddin Lada; Ag Asri Hj Ag Ibrahim (2011)
The objective of the paper is to explore the factors that encourage students to adopt social network sites (SNS) in Malaysia and to use the study’s findings to develop guidelines for SNS providers on how to maximize the rate of adoption. A conceptual model of Technology Acceptance Model (TAM), Theory of Planned Behaviour (TPB) and intrinsic motivation is proposed and empirically tested in the context of SNS usage. Structural Equation modelling was used on the survey data from 283 university students to test the model fit and corresponding hypotheses. The results show that both TAM and TPB were supported in their predictions of SNS usage intention and perceived enjoyment is a more significant antecedent of attitude as compared to perceived usefulness. Other than communicating with others, the users are looking for fun and enjoyment from using SNS. The relationships between the factors were also presented. Theoretical and managerial implications are discussed at the end of the article. The paper has addressed two limitations that provide opportunities for other researchers to explore them in depth in the future in the similar field of social network sites (SNS). The JIBC August 2011, Vol. 16, No.2 - 3 - limitations are presented in the conclusion’s part. For researchers, this paper provides a framework to identify and understand the way the potential key factors contribute to the adoption of SNS. For practitioners, this framework lists the features that specifically attract SNS users. Understanding users’ preferences is of major importance in ebusinesses for making strategic decisions to increase user satisfaction, as well as improving the performance of the business.